Synergistic effects of Rhynchosia nulubilis and Polygonum multiflorum extract combination on cell proliferation via targeting IGFBP-1 & NT-3 and cytotoxicity suppression in testosterone-induced human dermal papilla cells - Jiwon Seo; Chanhyeok Jeong; Jung Han Yoon Park; Chang Hyung Lee; Ki Won Lee (PLoS ONE, 2025)
This study examines the synergistic effects of extracts from Rhynchosia nulubilis (RN) and Polygonum multiflorum (PM) on the proliferation of human dermal papilla cells (hDPCs) and the alleviation of testosterone-induced cytotoxicity. Human dermal papilla cells (hDPCs) were treated with varying concentrations of RN and PM extracts, administered both individually and in multiple combinations at different ratios. The findings indicated that a 4:1 combination of RN and PM extracts significantly enhanced hDPC proliferation relative to the individual extracts, particularly in the presence of testosterone, which induced cytotoxicity. A significant synergistic effect was observed at a 4:1 ratio, resulting in the creation of a human growth factor array to identify targets associated with this synergy. The combined-extract group exhibited elevated levels of two significant growth factors: insulin-like growth factor-binding protein-1 (IGFBP-1) and neurotrophin-3 (NT-3). This was additionally validated through Western blot analysis. HPLC analysis identified six compounds and screening was conducted. As a result, genistein derived from RN and 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (2354-T2G) sourced from PM may be responsible for these effects. This is the first study to illustrate the significant synergistic effect of the combination of RN and PM, suggesting a potential treatment strategy that boosts the efficacy of natural compounds through synergy. The results suggest that the combined extracts could be useful as an effective treatment strategy for hair loss and associated disorders. Furthermore, this synergy-based approach has potential applications in future research on natural products.